"That's Jesus's Intent, and That Was Our Intent Too!": African Migration, Race, and US Missions. (April 2023) - Akano, Kimberly
In this essay, I analyze the intersection of African migration, race, and Christianity in the United States to highlight the 1960s as a pivotal moment of African immigrant influence on US missions. Rather than serving as pawns in a US-centric debate about race and missions, African immigrants were key players given their firsthand racialized encounters and their efforts to link racial discord in the US with US missions in Africa. By situating this discussion in the 1960s—a time before the emergence of formalized African immigrant churches—this essay illuminates a longer history of African immigrant influence on US Christianity.